HIIT Induces Stronger Shifts within the Peripheral T Cell Compartment Independent of Sex - Proschinger, Sebastian; Schenk, Alexander; Metcalfe, Alan J.; Zimmer, Philipp (International Journal of Sports Medicine, 2023)
Acute exercise induces changes within the T-cell compartment, especially in cytotoxic CD8+ memory subsets, depending on exercise intensity and duration. It is unclear whether exercise-induced changes in major T-cell subsets differ in response to acute high-intensity interval training (HIIT) or moderate-intensity continuous training (MICT) and whether sex-specific effects exist. Twenty-four recreationally active runners (females: n=12, 27.8±4.1years, 54.4±4.6 ml*kg-1*min-1; males: n=12, 31.6±3.8years, 58.9±7.7 ml*kg-1*min-1) participated in this randomized controlled crossover study, and conducted an energy- and duration-matched HIIT and MICT session. Blood was sampled before (T1), immediately (T2) and 1 h after exercise (T3). Flow cytometry was used to identify T-cell populations. HIIT decreased the proportion of CD8+ T-cells more pronounced at T3 compared to MICT (p=0.007), induced a significantly stronger increase in the CD8+ effector memory (TEM) cell proportion at T2 (p=0.032), and decreased CD4+ central memory proportion more pronounced at T2 (p=0.029). A decrease below baseline CD8+ TEM proportion at T3 was observed only after HIIT (p<0.001). No interaction effects between sexes were revealed. Taken together, HIIT represents a more potent stimulus to induce shifts mainly within the cytotoxic CD8+ T-cell compartment, thereby giving implications to investigate the role of HIIT on the cell´s effector phenotype and function in more detail.
Keywords: high-intensity interval training; T cells; gender; acute exercise; randomized controlled trial